Hubungan antara Kepercayaan Diri dengan Penyesuaian Sosial pada Mahasiswa Universitas Ma’soem Angkatan 2022 - Priatna, Ira Mirna (Jurnal Dimamu, 2024)
Students are often faced with adjustment problems such as acceptance and rejection in interactions with their environment. Apart from that, individuals also tend to expect themselves to develop for the better. This can be realized if individuals understand their abilities by having confidence, courage and self-confidence. This research aims to analyze the extent of the positive relationship between self-confidence and social adjustment of Ma'soem University students class of 2022. This research uses quantitative correlational methods with a population of 416 and a research sample of 204 students using stratified random sampling techniques. The measuring instruments used are a self-confidence scale based on aspects from Lauster (2012) and a social adjustment scale based on aspects from Hurlock (2013). The research results show a significance value (p) that is much smaller than 0.05 (0.000 < 0.05) and a correlation coefficient value of 0.689. Thus, there is a positive relationship between self-confidence and the social adjustment of Ma'soem University students class of 2022 which is relatively strong. Students with high levels of self-confidence tend to have better social adjustment.